2022
DOI: 10.1007/s00170-022-09630-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a titanium alloy outer ring self-lubricating spherical plain bearing by a two-step extrusion forming process

Abstract: Self-lubricating spherical plain bearing is a key component widely used in aerospace eld. The spherical plain bearing made of titanium alloy has lighter weight and better corrosion resistance. In order to manufacture the outer ring of self-lubricating spherical plain bearing with titanium alloy, a two-step extrusion forming process was proposed. Taking GE15DE1TK spherical plain bearing as an example, the nite element simulation model of the forming process was established, the forming test was carried out, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Using special lubrication methods or additives can effectively reduce the friction coefficient and friction losses of rolling bearings, providing good lubrication effects and prolonging the service life of bearings. Among these, materials such as solid paraffin (Dawari et al , 2022), hydrogenated diamond-like carbon coatings (Zhou et al , 2022), titanium alloys (Zhao et al , 2022a), self-lubricating polymer composites (Rodiouchkina et al , 2022; Zhao et al , 2022b), molybdenum disulfide and its composites (Yang et al , 2023; Gokce et al , 2021; Yang et al , 2022; Bhardwaj et al , 2021), polytetrafluoroethylene (PTFE) composites (Gungor and Demirer, 2022; Beckford et al , 2011; Deleanu and Georgescu, 2015; Feng et al , 2021; Lin et al , 2021; Trabelsi et al , 2016), graphene materials (Jin et al , 2023; Mao et al , 2018; Wu et al , 2021a; Jin et al , 2021) and alumina (Al 2 O 3 ) composites (Zhang et al , 2016; He et al , 2020; Tong et al , 2022) have demonstrated excellent anti-wear performance and tribological characteristics. However, the method of storing composite solid lubricants in bearing grooves has yet to receive attention.…”
Section: Introductionmentioning
confidence: 99%
“…Using special lubrication methods or additives can effectively reduce the friction coefficient and friction losses of rolling bearings, providing good lubrication effects and prolonging the service life of bearings. Among these, materials such as solid paraffin (Dawari et al , 2022), hydrogenated diamond-like carbon coatings (Zhou et al , 2022), titanium alloys (Zhao et al , 2022a), self-lubricating polymer composites (Rodiouchkina et al , 2022; Zhao et al , 2022b), molybdenum disulfide and its composites (Yang et al , 2023; Gokce et al , 2021; Yang et al , 2022; Bhardwaj et al , 2021), polytetrafluoroethylene (PTFE) composites (Gungor and Demirer, 2022; Beckford et al , 2011; Deleanu and Georgescu, 2015; Feng et al , 2021; Lin et al , 2021; Trabelsi et al , 2016), graphene materials (Jin et al , 2023; Mao et al , 2018; Wu et al , 2021a; Jin et al , 2021) and alumina (Al 2 O 3 ) composites (Zhang et al , 2016; He et al , 2020; Tong et al , 2022) have demonstrated excellent anti-wear performance and tribological characteristics. However, the method of storing composite solid lubricants in bearing grooves has yet to receive attention.…”
Section: Introductionmentioning
confidence: 99%